Clean Ganga And Sustainable Development (Journal of Namibian Studies : History Politics Culture, 2022)
Having an exceptional spot in each heart of Indian people, River Ganga is the important holy stream in our country with a special verifiable, social and otherworldly importance. The waterway other than advancing the huge grounds of Gangetic fields it likewise supports 50 significant Indian urban communities and many more modest towns. The feeders can possibly create adequate hydropower to help India's energy supplies. The stream can possibly turn into a dynamic stream to convey products and individuals across significant distances. That is the solitary waterway bowl in India that is asset rich with bunches of excess water still accessible. In spite of this notable status and strict legacy, the Ganga today is confronting impressive contamination pressures, alongside the orderly dangers to its biodiversity and natural maintainability. The Holy Ganges is now dirty and polluted water body full of anthropogenic dirt in the form of industrial effluents, human waste and plastic. Pollution loads of heavy weights, over-reflection in the lean season for broad water system, contending water requests and redirections and obstacles in the standard and feeders have destroyed ruin upon the soundness of the stream & its capacity to feed the large numbers of individuals who live & work in the bowl (Ruhl, 2015).